VEGF-D downregulation in CA1 pyramidal neurons exerts asymmetric changes of dendritic morphology without correlated electrophysiological alterations - Maurer, Jana; Yáñez, Antonio; Bengtson, C. Peter; Bading, Hilmar; Draguhn, Andreas; Mauceri, Daniela; Both, Martin (Neuroscience, 2020)
The morphology of dendritic arbors determines the location, strength and interaction of synaptic inputs. It is therefore important to understand the factors regulating dendritic arborization both during development and in situations of physiological or pathological plasticity. We have recently shown that VEGF-D (Vascular Endothelial Growth Factor D) is required to maintain length and complexity of basal dendrites in mouse hippocampal pyramidal cells. Lack of VEGF-D resulted in long-term memory deficits, suggesting a link between dendritic morphology and cognitive function. Here, we compared the effect of VEGF-D expression on basal versus apical dendrites of CA1 pyramidal cells, as well as its importance for synaptic processing of network oscillations. We report opposing, layer-specific effects of VEGF-D knockdown which resulted in shrinkage of basal and increased complexity of apical dendrites. Synaptic potentials and layer-specific voltage gradients during network oscillations remained, however, unaltered. These findings reveal a high spatial selectivity of VEGF-D effects at the sub-cellular level, and strong homeostatic mechanisms which keep spatially segregated synaptic inputs in a balance.